Synthesis and intramolecular nitrile oxide cycloaddition of 3,5 `-ether-linked pseudooligosaccharide derivatives: an approach to chiral macrooxacycles - Sengupta, J.; Mukhopadhyay, R.; Bhattacharjya, A.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Journal of Organic Chemistry, 2005)
[GRAPHIC] 3,5'-Ether-linked pseudooligopentose derivatives were synthesized for the first time from readily available carbohydrate precursors. The 1,2-isopropylidene-protected ether-linked oligopentoses are potentially important as precursors of novel RNA analogues. Intramolecular cycloaddition of the nitrile oxides prepared from these derivatives led to the diastereoselective formation of chiral isoxazolines fused to 10-16-membered oxacycles. The stereochemistry of some of these isoxazolines was established by X-ray diffraction and NOESY analysis.

Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.